Structural, dielectric, ferroelectric and optical properties of PBCT, PBST and PCST complex thin films on LaNiO3 metallic conductive oxide layer coated Si substrates by the CSD technique - Pontes, D. S. L.; Chiquito, A. J.; Pontes, F. M. [UNESP]; Longo, E. [UNESP] (Elsevier B.V., 2014)
Ferroelectric thin films and LaNiO3 (LNO) metallic conductive oxide thin films were prepared by a chemical solution deposition (CSD) method. PBCT60, PBST60 and PCST60 ferroelectric thin films were grown on different structures such as LNO/Si and single-crystalline quartz SiO2 (X-cut) substrates. The LNO layer acts as the bottom electrode for the electrical measurements. X-ray diffraction (XRD) analysis shows that LNO thin films on Si substrates and PBCT60, PBST60 and PCST60 thin films on LNO/Si structures are poly-crystalline with a moderate (110)-texture and a complete perovskite phase. LNO, PBCT60, PBST60 and PCST60 thin films have a continuous, dense and homogenous microstructure with a grain size on the order of 50-80 nm. Electrical resistivity-dependence temperature data confirm that LNO thin films display a good metallic character over a wide large range of temperatures. Optical characteristics of PBCT60, PBST60 and PCST60 thin films have also been investigated using ultraviolet-visible (UV-vis) spectroscopy in the wavelength range of 200-1100 nm. Ferroelectric thin films show a direct allowed optical transition with optical band gap values on the of order of 3.54, 3.66 and 3.89 eV for PBCT60, PCST60 and PBST60 thin films deposited on a SiO2 substrate, respectively. Good dielectric and ferroelectric properties are reported for ferroelectric thin films deposited on the LNO layer as bottom electrodes. Au/PBCT60/LNO/Si, Au/PBST60/LNO/Si and Au/PCST60/LNO/Si multilayer structures show a hysteresis loop with remnant polarization, P-r, of 9.6, 6.6 and 4.2 mu C/cm(2) at an applied voltage of 6 V for PBCT60, PBST60 and PCST60 thin films, respectively. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Thin films; LaNiO3; Electrical properties; Chemical solution deposition